Sravnitel'nyj analiz pokazatelej funkcional'noj podgotovlennosti sportsmenov, specializirujušcichsja v pulevoj i stendovoj strel'be - Tarasova, L. V.; Kryazhev, V. D.; Pankov, V. A. (Vestnik sportivnoj nauki; Sports science bulletin, 2018)
The work identified informative indicators of functional fitness of skilled shooters, men and women, specializing in bullet and trap shooting. Informative indicators of fitness at the precompetitive stage are: hemodynamics of the parameters of the vascular system of the heart rate (in work and orthoprobe), hemodynamics of indicators of systolic and diastolic AP (in orthoprobe) when the body position changes; indicators of the functional reserves of the cardiovascular system in the process of sports training. At the competitive stage: the duration of breath holding in the Genchi test, hemodynamics of the parameters of the vegetative-vascular system of the heart rate (at rest, at work, and in response to a change in body position); hemodynamics of the orthostatic reaction of diastolic AP and HR, with a change in body position; reserve capabilities of the respiratory system and respiratory breathing (rest/exhalation); reserve capabilities of respiratory function (at rest and on inspiration).